Staphylococcus aureus chromosomal mutation plaC1 amplifies plasmid pT181 by depressing synthesis of its negative-effector countertranscripts. - Iordanescu, S (1989)
A Staphylococcus aureus chromosomal mutation, plaC1, which leads specifically to the amplification of plasmid pT181 has previously been described (S. Iordanescu, Plasmid 10:130-137, 1983). The mechanism by which plaC1 amplifies plasmid pT181 has been approached in two ways: determination of the plasmid region required for the specific response to the plaC1 mutation and evaluation of different parameters of pT181 replication control by using transcriptional and translational fusions with the beta-lactamase gene as an indicator gene. The results obtained indicate that the control region of plasmid pT181 represents the target of the plaC1 effect, which acts primarily by depressing the synthesis of plasmid pT181 countertranscripts, those small, untranslated RNA molecules playing the roles of negative effectors in the replication control mechanism of the plasmid. In turn, the reduction in countertranscript synthesis leads to an increase in the production of the initiator protein RepC, which is limiting for plasmid replication, and a higher plasmid copy number.